Parallels in Immunometabolic Adipose Tissue Dysfunction with Ageing and Obesity - Trim, William; Turner, James E.; Thompson, Dylan (Frontiers in Immunology, 2018)
Ageing, like obesity, is often associated with alterations in metabolic and inflammatory processes resulting in morbidity from diseases characterised by poor metabolic control, insulin insensitivity, and inflammation. Ageing populations also exhibit a decline in immune competence referred to as immunosenescence, which contributes to, or might be driven by chronic, low grade inflammation termed ‘inflammageing’. In recent years, animal and human studies have started to uncover a role for immune cells within the stromal fraction of adipose tissue in driving the health complications that come with obesity, but relatively little work has been conducted in the context of immunometabolic adipose function in ageing. It is now clear that aberrant immune function within adipose tissue in obesity—including an accumulation of pro-inflammatory immune cell populations—plays a major part in the development of systemic chronic, low-grade inflammation, as well as limiting the function of adipocytes leading to an impaired fat handling capacity. As a consequence, these changes increase the chance of multi-organ dysfunction and disease onset. Considering the important role of the immune system in obesity-associated metabolic and inflammatory diseases, it is critical to further understand the interplay between immunological processes and adipose tissue function, establishing whether this interaction contributes to age-associated immunometabolic dysfunction and inflammation. Therefore, the purpose of this article is to summarise how the interaction between adipose tissue and the immune system changes with ageing, likely contributing to the age-associated increase in inflammatory activity and loss of metabolic control. To understand the potential mechanisms involved, parallels will be drawn to the current knowledge base derived from investigations in obesity. We will also highlight gaps in research and propose potential future directions based on the current evidence.